MENDETEKSI KECURANGAN LAPORAN KEUANGAN DENGAN KOMPONEN FRAUD HEXAGON - Siti Nurkumala (2023)
This study aims to determine the effect of the fraud hexagon components reviewed through financial targets, director changes, ineffective monitoring, auditor changes, numbers of ceo's picture, state owned enterprises on fraudulent financial statements in non-financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2022. This research is a quantitative research type that uses secondary data in the form of financial reports obtained from the official website of the IDX and the company's official website. This study used a sample of 532 companies. The technique for analyzing the data in this study used descriptive statistical tests, classical assumption tests and partial statistical tests (t-test) using the STATA 14 application with the help of Microsoft Excel. Based on the results of the tests that have been carried out, it shows that changing auditors has a significant positive effect on fraudulent financial statements. Meanwhile, changes in directors and government ownership have a significant negative effect on fraudulent financial statements. Keyword: fraudulent financial statement, ,financial targets, director changes, ineffective monitoring, auditor changes, numbers of ceo's picture, state owned enterprises